Perceptions of EFL Teachers in Esfahan High Schools Towards Professional Knowledge and Skills Development Tthrough Short-Term in-Service Programmes - Renani, Ghasemali Azadi (2011)
This study is an attempt to identify the perceptions of EFL teachers in Esfahan high schools towards professional knowledge (PK) and professional skills (PS) development through a short-term in-service development programme (SIDP). The SIDP for EFL teachers is assumed to be of crucial importance in updating teachers’ PK and PS. EFL context in which English is merely taught as a subject in school but neither used as a medium of instruction in education nor as a language of communication calls for the need of proficient non-native teachers. This fact highlights the role of SIDPs supporting teachers to survive in the teaching profession. The present survey study attempts to identify the significant difference in the perceptions of EFL teachers in Esfahan high schools towards the SIDP. The two main defined objectives for this study are to determine: 1) whether there is any significant difference between EFL teachers’ gender, academic qualification, teaching experience, and age and their perception towards the PK presented in a SIDP and 2) whether there is any significant difference between EFL teachers’ gender, academic qualification, teaching experience, and age and their perception towards the PS presented in a SIDP. The data were collected through questionnaire and interview using a quantitative research method with a descriptive design and cross-sectional method. As the sample, 256 Iranian EFL teachers in Esfahan high schools participated in the study and filled up questionnaires and 20 EFL teachers participated in interviews. The results were analysed through both descriptive and inferential statistics. The findings on sample’s gender, academic qualification, teaching experience, and age indicate: a) there is no significant difference in the PK between male and female teachers. The attitude of both groups is positive. However, there is significant difference in the PS between male and female teachers. The attitude of the male teachers is moderate while the attitude of the female teachers is positive; b) there is significant difference in the PK between Bachelors and Masters. EFL teachers holding Bachelor degree show positive attitude towards the programme while those holding Master degree show negative attitude. Likewise, there is significant difference in the PS between Bachelors and Masters. EFL teachers holding Bachelor degree show positive attitude towards the programme while those holding Master degree show negative attitude; c) regarding the PK, although all three groups with different teaching experience perceive SIDP as positive, there is difference among the three groups. The least experienced teachers show the most positive attitude and the most experienced ones show the least positive attitude. Regarding the PS, the groups with the least and moderate experience perceive SIDP as positive while the most experienced group perceives SIDP as negative; d) the youngest teachers show the most positive attitude and the eldest ones show the least positive attitude towards PK. The young and mid-age groups perceive PS as positive while the old group perceives it as negative. Moreover, the results of the interviews indicate that EFL teachers perceive PK presented in the SIDP better than PS presented in the SIDP. In general, EFL teachers in Esfahan high schools perceive the PK presented in the SIDP as positive and perceive the PS presented in the SIDP as moderate. In the light of findings, the implications of the study concern the need for education policy-makers to outline more practice-based SIDPs, for teacher educators to revisit development strategies by welcoming EFL teachers’ challenges faced in the classroom, for EFL teachers to involve actively in the SIDPs to widen their PK and enhance their PS and identify immediate needs of teaching.